Motives of «Letters from the Farm» by Kulish in a Story by I. Nechui-Levicky«Unequal Paths» - Kalantaievska H.; Sypchenko I. (Philological Treatises, 2020)
Kulish considered the farmer traditions in the context of natural harmonious life and observance of the laws of Scripture as an effective defense against the victorious advance of global urban civilization on the spiritual and moral-ethical space of his contemporary. The writer's attitude to the threats to the Ukrainian society, which went from cultivating consumer tastes, the desire to compete in the pursuit of comfort and fashion, supported in his work I. Nechui-Levitsky, tracing in the story "Unequal paths" the path of rapid decline of two families (rural and countryside), as a result of their capture of the false values of the world of accumulation and vanity. The proposed article traces the organic connection and creative interpretation of P. Kulish's views expressed in the journalistic series "Letters from the Farm", with the ideological sounding of I. Nechuy-Levitsky's "Unequal Paths", in which the author explored the causes and catastrophic consequences of neglecting genus traditions and choosing it as priorities for self-centeredness and hedonism. Attention is drawn to the close connection of the influence of irradiated Kiev (or St. Petersburg) on the heroes of the work (Vanatovich, Mikhail Ulasevich) with their internal readiness to become werewolf adapters for the career, state awards or approving reviews in urban private salons. The article analyzes the writer's characteristics and sketches of rural and Kiev bohemian life on emotional, psychological, household, economic, custom, value, cultural and educational levels, emphasizes on presented in the work conflict not only the generation of parents and children, but also on conflict - values colonial morality and entertainment culture, on the one hand, and traditions of the genus and true education, on the other. Also it is showed the figures of new heroes of society, whose life paths are directed not to the search for pleasure, but to help their people through enlightenment and introduction of modern technologies in agriculture.